2015
DOI: 10.1002/mnfr.201500317
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in skin carotenoid deposition and acute UVB-induced skin damage in SKH-1 hairless mice after consumption oftangerinetomatoes

Abstract: Scope-UVB exposure, a major factor in the development of skin cancer, has differential sex effects. Tomato product consumption reduces the intensity of UVB-induced erythema in humans, but the mechanisms are unknown.Methods and results-Four week old SKH-1 hairless mice (40 females, 40 males) were divided into two feeding groups (control or with 10% tangerine tomatoes naturally rich in UVabsorbing phytoene and phytofluene) and two UV exposure groups (with or without UV). After 10 weeks of feeding, the UV group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…This held true even in mice not exposed to UV denoting that there are fundamental differences in the physiology of skin between the sexes. There was no significant differences in skin fold thickness between the control and tomato diets for either sex after exposure to UV, consistent with previous reports from our group (data not shown) 14 .…”
Section: Resultssupporting
confidence: 93%
“…This held true even in mice not exposed to UV denoting that there are fundamental differences in the physiology of skin between the sexes. There was no significant differences in skin fold thickness between the control and tomato diets for either sex after exposure to UV, consistent with previous reports from our group (data not shown) 14 .…”
Section: Resultssupporting
confidence: 93%
“…Goralczyk and Wertz [11] identified some major mechanisms, among which inhibition of lipid peroxidation, inhibition of UVA-induced expression of heme oxygenase 1, prevention of mitochondrial DNA mutations, inhibition of metalloproteases and photoimmune modulation. Recent experiments in hairless mice subjected to UVB radiation indicated that tangerine tomato carotenoids may exert beneficial effects by attenuating DNA-damage and inflammation, with interesting differences between males and females [180]. Noticeably, new possible mechanisms are hypothesized thanks to the use of omics technologies for the study of changes in gene expressions associated to exposure to carotenoids.…”
Section: Carotenoids and Photoprotectionmentioning
confidence: 99%
“…The results indicated that the levels of carotenoids in skin and blood were higher in female mice. With respect to the photoprotective mechanism, UVB-induced carotenoids were associated with a reduction in inflammation and CPDs [ 202 ]. In a study by Cooperstone et al, mice were provided with a tomato-containing diet for 35 weeks.…”
Section: Role Of Whole Fruits and Vegetables In Skin Cancer Prevenmentioning
confidence: 99%